Outcomes of achieving lupus low disease activity state and damage accrual in childhood-onset systemic lupus erythematosus - Na Nakorn K. (2023)
Introduction: At present, the treat-to-target approach has been proposed with the lupus low disease activity state (LLDAS) as an achievable target. Objectives: To determine damage accrual and baseline clinical characteristics associated with achieving LLDAS within 12 months of treatment in patients with childhood-onset systemic lupus erythematosus (c-SLE). Methods: This retrospective cohort study was conducted at the largest university-based tertiary referral center in Thailand. Data of c-SLE patients (≤ 18 years) at diagnosis who were followed ≥ 12 months during January 2009 to December 2019 were collected. SLE disease status was categorized into LLDAS and non-optimally controlled state. SLEDAI-2K score was used to assess disease activity. Damage accrual was assessed by a pediatric version of the SLICC/ACR damage index. Results: A total of 232 c-SLE patients (85.8% female) were included. At 12 months of treatment, 109 (47%) patients achieved LLDAS. Damage accrual was observed in 93 (40.1%) patients at the mean follow-up time of 6.2 ± 3.7 years. Damage accrual was significantly lower in patients who achieved LLDAS within 12 months than in those non-optimally controlled (p = 0.002). The median time to achieving LLDAS was 12.6 months (95%CI: 11.19–13.97). The median time to achieving LLDAS was significantly shorter in those without renal involvement (10.8 months, 95%CI: 9.62–12.00 vs. 15.6 months, 95%CI: 13.76–17.52, respectively; p = 0.044). Multivariable logistic regression analysis revealed absence of renal involvement as the predictor of achieving LLDAS within 12 months of treatment (aOR: 2.430, 95%CI: 1.420–4.158; p = 0.001). Conclusions: Achieving LLDAS within 12 months of treatment was associated with lower damage accrual. Absence of renal involvement was the predictor of achieving LLDAS within 12 months of treatment.Key Points• LLDAS is a promising and achievable treatment target in c-SLE.• Achieving LLDAS within 12 months of treatment is associated with lower damage accrual.• Absence of renal involvement is the predictor of achieving LLDAS within 12 months of treatment.